Fungsi Manajemen Menurut Al-Qur’an - Sonya Liani Nasution; Euis Indah Kesuma Ningsih; Wahyu Dermawan; Yusuf Hadi Jaya; Asnil Aida Ritonga (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
Management is the science and art of managing the process of implementing human resources based on their functions and duties effectively and efficiently to achieve a certain goal. The success of a leader is mastering a management function in a good company or agency, so a leader is needed who is able to master and act professionally towards the management function (POAC), namely Planning, Organizing, Actuating (Directing). and Controlling (Supervision). In the perspective of the Koran there are also four parts of the management function, namely planning contained in surah Al Isra' verse 36, organizing contained in surah Al-Anfal verse 46, directing contained in surah An-Nahl verse 125 and lastly Supervision is contained in surah An-Nisa verse 1. Keywords: Management Functions, Planning, Organizing, Actuating, Controlling, POAC in Al Quran